1013. Predicting RSV Efficacy for MK-1654 in Temperate and Tropical Climates using MBMA and Clinical Trial Simulation to Account for Seasonal Differences in RSV Force-of-Infection. (4th December 2021) - Plock, Nele; Lommerse, Jos; Maas, Brian M; Chen, Jingxian; Bellanti, Francesco; Qin, Li; Witjes, Han; Pierrillas, Philippe; Railkar, Radha; Aliprantis, Antonios O; Vora, Kalpit A; Gao, Wei; et al.
Abstract: Background: MK-1654 is a respiratory syncytial virus (RSV) F glycoprotein neutralizing monoclonal antibody under development to prevent RSV infection in infants. A model-based meta-analysis (MBMA) describing the relationship between RSV serum neutralizing activity (SNA) and clinically relevant endpoints (e.g. incidence rates) in humans, including lower respiratory tract infection (LRI) in infants, was presented previously. This model accounted for variable exposure to RSV over the course of the season through a force-of-infection (FOI) function modulating the overall risk of RSV infection over time. The objective of the current work was to determine whether variations in regional seasonality would impact the efficacy of a clinical trial evaluating MK-1654. Methods: A FOI function to describe the degree of RSV exposure as a function of time was created by fitting epidemiological data to a Gaussian function added to a constant baseline value. Clinical trial simulations were conducted using the MBMA to predict seasonal incidence rates (IR) of RSV medically attended lower-respiratory tract infection (MALRI) and efficacies for a range of MK-1654 doses in both temperate and tropical regions. Results: Epidemiological data was well captured by the FOI function. Clinical trial simulations indicated that seasonal IRs of RSV were sensitive to differences in the FOI represented by temperate and tropical regions; however, there was no substantial impact on efficacies across MK-1654 dose levels. Consistent with predictions for a temperate climate, MK-1654, when administered at the start of the RSV season in a region with a tropical climate, was also predicted to maintain high efficacy ( > 75%) for the prevention of RSV MALRI for 150 days. Conclusion: Simulations indicated that while FOI is a substantial driver of overall RSV incidence rates, MK-1654 efficacy in a late-stage clinical trial is likely to be high, regardless of regional variations in RSV. Disclosures: Nele Plock, PhD, Certara (Employee, Shareholder)Merck & Co., Inc. (Independent Contractor) Jos Lommerse, PhD, Certara (Employee, Shareholder)Merck & Co., Inc. (Independent Contractor) Brian M. Maas, PharmD, Merck & Co., Inc. (Employee, Shareholder) Jingxian Chen, PhD, Merck & Co., Inc. (Employee, Shareholder) Francesco Bellanti, PhD, Certara (Employee, Shareholder)Merck & Co., Inc. (Independent Contractor) Li Qin, PhD, Certara (Employee, Shareholder)Merck & Co., Inc. (Independent Contractor) Han Witjes, PhD, Certara (Employee, Shareholder)Merck & Co., Inc. (Independent Contractor) Philippe Pierrillas, PhD, Certara (Employee, Shareholder)Merck & Co., Inc. (Independent Contractor) Radha Railkar, PhD, Merck & Co., Inc. (Employee, Shareholder) Antonios O. Aliprantis, MD, PhD, Merck & Co., Inc. (Employee, Shareholder) Kalpit A. Vora, PhD, Merck & Co., Inc. (Employee, Shareholder) Wei Gao, PhD, Merck & Co., Inc. (Employee, Shareholder) Luzelena Caro, PhD, Merck & Co., Inc. (Employee, Shareholder) S. Y. Amy Cheung, PhD, Certara (Employee, Shareholder) Jeffrey R. Sachs, PhD, Merck & Co., Inc. (Employee, Shareholder)